The Effect of Peer Groups on Society’s Stigma Perception of PWLA (People Living With HIV/AIDS) at Cakap Foundation Group WPA Turen - Sasono, Tri Nurhudi; Nurbadriyah, Wiwit Dwi; Aditya, Ronal Surya; Ulyana, Dina (International Journal of Psychosocial Rehabilitation, 2020)
-- PWLA is used to refer to people living with HIV/AIDS. It is not uncommon for PWLA to possess negative habits. The act of labeling or viewing them negatively has become a sort of social stigma. In its practice, the stigma may result in discrimination such as not recognizing PWLA as human beings worthy of dignity. One of the efforts to avoid such discrimination is through healthcare-related and educational approaches through peer groups with the aim of raising society’s awareness of HIV-AIDS. Therefore, PWLA can be accepted by society. The purpose of this study was to reduce the community's negative stigma towards PWLA. Pre-experimental action research with a one group pretest-posttest design was used in this study. The sample was selected using a simple random sampling technique. The independent variable was peer support and the dependent variable was the respondent's stigma. The data was collected using a questionnaire that had good validity and reliability. The data was collected using questionnaires focused on the results of the modified HIV stigma scale by Berger with as many as 40 items. The measurements were done 2 times with the 48 respondents who were people living with HIV-AIDS at CAKAP Foundation Talok Turen Village, Malang District. Peer group support was given 4 times for 1 month with 1-2 hours set aside for the meeting duration. The data was analyzed in a bivariate and comparative manner using the Wilcoxon signed rank test for normally undistributed data at a significance level of p